(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
This scientific article, written about the effectiveness of treatment of rickets, is dedicated to the study of methods of treatment of rickets, a disease characterized by a disorder of bone growth and development as a result of calcium and phosphate metabolism disorders. This article analyzes modern drugs used in the treatment of rickets, vitamin D and its analogues, as well as alternative treatment methods and their effectiveness. Research results, treatment effectiveness and side effects are presented. The results of scientific studies on the identification, diagnosis and prevention of clinical signs of rickets were analyzed. The article emphasizes the importance of individual approach to prevention and treatment of rickets among children and adolescents.